Pengelolaan Pendapatan Asli Daerah Di Kabupaten Bima - Andi Andi; Ansyari Mone; Adnan Ma'ruf (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
The purpose of this study was to explore the Management of Local Revenue (PAD) in Kabupaten Bima in accordance with Law No. 33 of 2004 concerning the Regional Government in managing its own household. Type of qualitative research.Type of case study research. Data collection techniques are interviews, observation and documentation. The results of the study were that the management of PAD through planning, implementing and controlling taxes. while the strategy of increasing regional taxes and levies through identification and inventory of value and potential of regional assets, the existence of regional asset SIMs, asset supervision and involvement of internal auditors. ABSTRAKTujuan penelitian ini adalah untuk mendalami Pengelolaan Pendapatan Asli Daerah (PAD) di Kabupaten Bima sesuai dengan Undang-undang No. 33 Tahun 2004 tentang Pemerintah Daerah dalam mengurus rumah tangganya sendiri. Jenis penelitian kualitatif. Tipe penelitian studi kasus. Teknik pengumpulan data yaitu wawancara, observasi dan dokumentasi. Hasil penelitian bahwa pengelolaan PAD melalui Perencanaan, pelaksanaan dan pengendalian pajak. Sementara strategi peningkatan pajak dan retribusi daerah melalui Identifikasi dan inventarisasi nilai dan potensi aset daerah, adanya SIM aset daerah, pengawasan aset dan pelibatan auditor internal.